Assessing the Adjuvant Efficacy of Oral Gabapentin to Balanced Anaesthesia for Elective Surgeries in Dogs - Rajesh, Chendurpandi; Vishnugurubaran, Dhanakaran; Jayakumar, Kulandaivel; Vijayakaran, Karunakaran; Kaarthick, Damodaran; Thabsheera, Adiyattil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Oral gabapentin has been increasingly explored for its anaesthetic sparing properties in veterinary anesthesia. This study aimed to evaluate the efficacy of oral gabapentin as an adjunct in balanced anaesthesia in dogs undergoing elective surgeries, with a focus on its reduction in anaesthetic requirements. A total of 20 dogs brought for elective surgeries were selected and the selected animals were divided into two groups of 10 animals each, viz., group I and group II. Group II animals received oral gabapentin (10 mg/kg) as premedicant twice a day for two days before the surgery and one dose, 2 h before the surgery. Both groups were pre-medicated with dexmedetomidine and butorphanol, followed by induction with diazepam and ketamine and maintenance with isoflurane. Isoflurane concentrations were measured continuously during the surgical procedure. The gabapentin group showed a significant reduction in isoflurane requirements compared to the control group (p<0.05) indicating a notable isoflurane-sparing effect (57.34%). Oral gabapentin effectively reduces the requirement for isoflurane and provides superior analgesia in dogs undergoing elective surgeries. These findings support its use as an adjunctive agent in balanced anesthesia, offering both clinical and economic advantages.